The proposed Caroline ESA M3 mission to a Main Belt Comet. Issue 8 (15th October 2018) - Jones, Geraint H.; Agarwal, Jessica; Bowles, Neil; Burchell, Mark; Coates, Andrew J.; Fitzsimmons, Alan; Graps, Amara; Hsieh, Henry H.; Lisse, Carey M.; Lowry, Stephen C.; Masters, Adam; Snodgrass, Colin; et al.
Abstract: We describe Caroline, a mission proposal submitted to the European Space Agency in 2010 in response to the Cosmic Visions M3 call for medium-sized missions. Caroline would have travelled to a Main Belt Comet (MBC), characterizing the object during a flyby, and capturing dust from its tenuous coma for return to Earth. MBCs are suspected to be transition objects straddling the traditional boundary between volatile–poor rocky asteroids and volatile–rich comets. The weak cometary activity exhibited by these objects indicates the presence of water ice, and may represent the primary type of object that delivered water to the early Earth. The Caroline mission would have employed aerogel as a medium for the capture of dust grains, as successfully used by the NASA Stardust mission to Comet 81P/Wild 2. We describe the proposed mission design, primary elements of the spacecraft, and provide an overview of the science instruments and their measurement goals. Caroline was ultimately not selected by the European Space Agency during the M3 call; we briefly reflect on the pros and cons of the mission as proposed, and how current and future mission MBC mission proposals such as Castalia could best be approached.